Ab initio study of ferromagnetism induced by magnetic impurities in rutile TiO₂ - Errico, Leonardo Antonio (2004)
Using the first-principles density-functional approach, magnetic properties of Mn-, Fe-, Co-, and Ni-doped rutile TiO₂ were investigated for two different impurity concentrations (25% and 6.25%). Calculations were performed with the Full-Potential Linearized-Augmented Plane Waves (FLAPW) method, assuming that the magnetic impurities substitutionally replace the Ti ions. Our results show that the systems (with the exception of Ni-doped TiO₂) are ferromagnetic. We also found that polarization mainly occurs at the impurity sites, and the magnetic moments of the impurities are independent of the impurity concentration.